2013
DOI: 10.1002/2013jd019527
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aerosol optical depth between CALIOP and MODIS‐Aqua for CALIOP aerosol subtypes over the ocean

Abstract: [1] The Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) aerosol optical depth (AOD) has been compared with the Moderate Resolution Imaging Spectroradiometer (MODIS)-Aqua AOD using Level 2 products of both instruments. Such comparisons have been performed for five different aerosol subtypes classified by CALIOP algorithm, namely clean marine, dust, polluted dust, polluted continental, and biomass burning, over the ocean from June 2006 to December 2010. MODIS AOD at 550 nm (0.111 ± 0.079) for the collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 67 publications
9
47
0
Order By: Relevance
“…The CALIOP lidar ratio for dust (40 sr) is on the low end of the typical range of lidar ratios (40-60 sr) measured in Europe or Africa (Mattis et al, 2002;Tesche et al, , 2011Papayannis et al, 2008;Müller et al 2012;Esselborn et al, 2009), but is consistent with recent measurements of lidar ratio for dust from the Arabian Peninsula (Mamouri et al, 2013), and with earlier estimates based on AERONET observations (e.g., Cattrall et al, 2005). Recent studies have demonstrated that considering the source region of the dust, and any changes in its properties during transport, along with any other aerosol type it mixes with would likely provide a better estimate of lidar ratio (Schuster et al, 2012;Kim et al, 2014). However, accounting for these additional factors would require additional measurements and/or sources of information (e.g., back trajectories) that are not currently incorporated into the CALIOP data analysis scheme.…”
Section: Dustsupporting
confidence: 85%
See 1 more Smart Citation
“…The CALIOP lidar ratio for dust (40 sr) is on the low end of the typical range of lidar ratios (40-60 sr) measured in Europe or Africa (Mattis et al, 2002;Tesche et al, , 2011Papayannis et al, 2008;Müller et al 2012;Esselborn et al, 2009), but is consistent with recent measurements of lidar ratio for dust from the Arabian Peninsula (Mamouri et al, 2013), and with earlier estimates based on AERONET observations (e.g., Cattrall et al, 2005). Recent studies have demonstrated that considering the source region of the dust, and any changes in its properties during transport, along with any other aerosol type it mixes with would likely provide a better estimate of lidar ratio (Schuster et al, 2012;Kim et al, 2014). However, accounting for these additional factors would require additional measurements and/or sources of information (e.g., back trajectories) that are not currently incorporated into the CALIOP data analysis scheme.…”
Section: Dustsupporting
confidence: 85%
“…Schuster et al (2012) found CALIOP to agree within 13 % of AERONET with better agreement, within 3 %, if dust is excluded from the analysis. Kim et al (2014) used MODIS (Moderate Resolution Imaging Spectroradiometer) to evaluate CALIOP, finding CALIOP to be 63 % lower than MODIS. However, one limitation common to all previous CALIOP AOD investigations is that the comparisons used only total column AOD measured during daytime, when the CALIOP signal-to-noise ratio (SNR) is the lowest.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that differences in AE estimates from MODIS and CALIOP largely explain the discrepancy between two aerosol products. Previous studies indicate that MODIS and CALIOP AOD are poorly correlated (e.g., Costantino and Bréon, 2010;Kim et al, 2013;Kittaka et al, 2011;Ma et al, 2013). Our results suggest that differences in AOD retrievals can lead to differences in AE estimates and further affect AI and precipitation susceptibly estimates.…”
Section: S X_ai From Different Aerosol Productsmentioning
confidence: 65%
“…Unlike MODIS AE, which is directly reported in aerosol products, AE measurement for CALIOP is calculated based on AOD at 1.064 and 0.532 µm from the CAL_LID_L2_05kmALay product (Bréon et al, 2011). Our data screening for CAL_LID_L2_05kmALay follows a previous study by Kim et al (2013).…”
Section: Ai and Cdncmentioning
confidence: 99%
“…This may be different for different regions and time of year, thus adding to the uncertainty in the comparison. The CALIOP analysis may also misclassify aerosol as discussed by Kim et al (2013). The latter is largely avoided in this study by focusing on dust aerosol which has a relatively large depolarization ratio.…”
Section: Discussionmentioning
confidence: 99%